(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Anoplophora glabripennis (Motschulsky), also known as Asian Longhomed Beetle (ALB), has been recorded for the first time in Italy. It’s native to China and Korea, where it is considered as a serious pest of deciduous tree species particularly poplars, maples, and willows.